2020
DOI: 10.1002/ceat.201900339
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Hydrogen Production from Methane Partial Oxidation: Mechanism and Kinetic Study

Abstract: The multifunctional potential of a transition and noble metal catalyst supported on either a single support or combined oxide support in the catalytic partial oxidation of methane (CPOM) is reviewed. The close interaction and interfacial area between the metal, reducible oxide, and acidic support are highlighted, which are crucial for low‐temperature CPOM. The effects of the catalyst components and their preparation methods are considered. Their impact on the catalytic performance and stability on the CPOM rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 48 publications
(79 reference statements)
0
47
0
1
Order By: Relevance
“…In relation to the transportation sector, end-use fuel switch is a determinant to sector decarbonization. Some examples of biofuels are biodiesel, first-and second-generation bioethanol, bio-hydrogen, bio-methane and bio-dimethyl ether (bio-DME) (Srivastava et al 2020;Chauhan et al 2009;Hajilary et al 2019;Osman 2020). Furthermore, hydrogen produced through electrolysis using renewable energy is a potential renewable fuel for sector decarbonization.…”
Section: Renewable Energymentioning
confidence: 99%
“…In relation to the transportation sector, end-use fuel switch is a determinant to sector decarbonization. Some examples of biofuels are biodiesel, first-and second-generation bioethanol, bio-hydrogen, bio-methane and bio-dimethyl ether (bio-DME) (Srivastava et al 2020;Chauhan et al 2009;Hajilary et al 2019;Osman 2020). Furthermore, hydrogen produced through electrolysis using renewable energy is a potential renewable fuel for sector decarbonization.…”
Section: Renewable Energymentioning
confidence: 99%
“…However, landfilling is expensive, requires space and can have a negative environmental impact if not well managed due to the production of leachate, methane and carbon dioxide and other nuisances like flies, odour, and vermin like birds and rodents. Leachate could also pollute underground water and soil along with the release of methane which is a potent greenhouse gas with a short-term global warming potential that is 84 times more powerful than carbon dioxide 2 4 . On the other hand, using food waste as a potential source for the production of sustainable fuels will complete the full cycle of this waste stream sustainably and thus, directly support and facilitate the concept of the circular economy in the form of open-loop recycling 5 8 .…”
Section: Introductionmentioning
confidence: 99%
“…As far the production is concerned, fossil fuel is responsible for the majority of hydrogen production, out of which 60% is produced from dedicated primary hydrogen-producing facilities. It is also reported that around 71.27% of hydrogen is produced from natural gas (NG), 27.27% from coal, 0.7% from petroleum and the remaining 0.7% from water electrolysis [10][11][12]. Notably, the hydrogen production from fossil reformation is neither renewable nor carbon neutral as the production process involves high numbers of GHG footprints [4].…”
Section: Introductionmentioning
confidence: 99%